Model for Optimizing the Development of Aek Sijorni Natural Bath Tourism in South Tapanuli Regency - Novawati Siregar; Ruth Riah Ate Tarigan; Feby Milanie (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The Aek Sijorni Natural Bath in South Tapanuli Regency holds great potential as a regional tourism icon, with its tiered waterfalls and unique natural atmosphere. This study aims to formulate a model for optimizing tourism development based on sustainability, technology, and local community participation. A mixed methods approach was employed. The findings indicate that development of the area should focus on improving basic infrastructure, enhancing cleanliness, and providing additional facilities such as dining areas and recreational zones. Furthermore, strengthening digital promotion and actively involving the local community are proven to be key factors in creating a competitive and sustainable destination. Strategic recommendations are centered on multi-stakeholder collaboration and the use of information technology to generate broader economic and social impacts for the surrounding communities.